Preparation and investigation of copper-manganese mixed oxides as a high-efficiency catalyst for the azid-alkyne 1,3-dipalar cycloaddition reaction - Amini, Mojtaba; Salmani, Somaiyeh; Gautam, Sanjeev; Chae, Keun Hwa (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
The present work is developed for the catalysis of azide-alkyne 1,3-dipolar cycloaddition reaction with the aid of copper-manganese mixed oxides nanoparticles. The Cu/MnOx nanoparticles have been synthesized by a coprecipitation procedure. Characterization of Cu/MnOx nanoparticles was performed by various spectroscopic techniques, such as powder XRD, Energy dispersive X-ray spectroscopy (EDX) and SEM and TEM analyses. The azide-alkyne cycloaddition reactions successfully proceed under air in presence of the as-prepared copper-manganese mixed oxides nanoparticles. The methodology is advisable to a wide variety of various alkynes and benzyl halide moieties signifying its well suitability. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: REUSABLE CATALYST; 1,2,3-TRIAZOLES; NANOPARTICLES; OXIDATION; LIGAND